Mast cells in the pathophysiology of Duchenne muscular dystrophy in Golden Retriever dogs - Martins, Isabela M. [UNESP] (2020)
The Golden Retriever muscular dystrophy (GRMD) is one of the best models of Duchenne muscular dystrophy (DMD), with similar genotypic and phenotypic manifestations. Progressive proliferation of connective tissue in the endomysium of the muscle fibers occurs in parallel with the clinical course of the disease in GRMD animals. Previous studies suggest a relationship between mast cells and the deposition of fibrous tissue due to the release of mediators that recruit fibroblasts. The aim of this study was to evaluate the presence of mast cells and their relationship with muscle injury and fibrosis in GRMD dogs of different ages. Samples of muscle groups from six GRMD and four control dogs, aged 2 to 8 months, were collected and analyzed. The samples were processed and stained with HE, toluidine blue, and Azan trichrome. Our results showed that there was a significant increase in infiltration of mast cells in all muscle groups of GRMD dogs compared to the control group. The average number of mast cells, as well as the deposition of fibrous tissue, decreased with age in GRMD dogs. In the control group, all muscle types showed a significant increase in the amount of collagenous tissue. This suggests increased mast cell degranulation occurred in younger GRMD dogs, resulting in increased interstitial space and fibrous tissue in muscle, which then gradually decreased over time as the dogs aged. However, further studies are needed to clarify the role of mast cells in the pathogenesis of fibrosis.